Pengaruh Pelayanan Fiskus, Tarif Pajak, Dan Praktik Korupsi Trhadap Kepatuhan Pajak Dengan Good Corporate Governance (Gcg) Sebagai Variabel Moderasi (Studi Pada Umkm Di Pasar Bintaro Jakarta) - Trihana, Trihana; Sabaruddin, Sabaruddin (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p04, 2025)
This study aims to analyze the effect of tax authorities services, tax rates, and corrupt practices on tax compliance with Good Corporate Governance (GCG) as a moderating variable on MSMEs in Pasar Bintaro Jakarta. Tax compliance is an important aspect in maintaining the country's fiscal stability, but there are still various challenges such as the low quality of tax authorities services, burdensome tax rates, and high levels of corruption. using a quantitative approach with a survey method. Data were obtained through questionnaires distributed to MSME owners in Pasar Bintaro. Data analysis was carried out using multiple regression methods. The results of the study indicate that tax authorities services have a significant positive effect on tax compliance, while tax rates and corrupt practices have a significant negative effect. In addition, the implementation of GCG has been proven to be able to strengthen the positive effect of tax authorities services on tax compliance, as well as moderate the negative impacts of tax rates and corrupt practices. Keywords: Tax Service; Tax Rate; Corruption Practice; Tax Compliance; GCG.